2013
DOI: 10.1242/jeb.096834
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hydrogen peroxide production and mitochondrial respiration in skeletal muscle but not cardiac muscle of the green-striped burrowing frog, a natural model of muscle disuse

Abstract: Suppression of disuse-induced muscle atrophy has been associated with altered mitochondrial reactive oxygen species (ROS) production in mammals. However, despite extended hindlimb immobility, aestivating animals exhibit little skeletal muscle atrophy compared with artificially immobilised mammalian models. Therefore, we studied mitochondrial respiration and ROS (H 2 O 2 ) production in permeabilised muscle fibres of the green-striped burrowing frog, Cyclorana alboguttata. Mitochondrial respiration within sapon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
9
1
1
Order By: Relevance
“…Hypoxia acclimation of killifish reduced the rate of ROS release from liver mitochondria, akin to the effects of estivation on skeletal muscle mitochondria in burrowing frogs (Reilly et al, 2014), and we observed qualitatively similar effects of acclimation to constant hypoxia and intermittent hypoxia (Fig. 4).…”
Section: Hypoxia Acclimation Reduced Mitochondrial Ros Emissionsupporting
confidence: 69%
“…Hypoxia acclimation of killifish reduced the rate of ROS release from liver mitochondria, akin to the effects of estivation on skeletal muscle mitochondria in burrowing frogs (Reilly et al, 2014), and we observed qualitatively similar effects of acclimation to constant hypoxia and intermittent hypoxia (Fig. 4).…”
Section: Hypoxia Acclimation Reduced Mitochondrial Ros Emissionsupporting
confidence: 69%
“…This decrease in proton leak is greater than that seen in overwintering common frogs (see Overwintering Ectotherms, earlier) whereas mammalian heterotherms typically show no decrease in proton leak during torpor (see Turning Down ATP Supply, earlier). The suppression of mitochondrial metabolism is not seen in all tissues, including cardiac muscle of the green-striped burrowing frog (238). This result should be viewed with caution, however, as it was obtained using saponin-permeabilized tissue sections (238).…”
Section: Estivating Ectothermsmentioning
confidence: 79%
“…The suppression of mitochondrial metabolism is not seen in all tissues, including cardiac muscle of the green-striped burrowing frog (238). This result should be viewed with caution, however, as it was obtained using saponin-permeabilized tissue sections (238). We found recently that the inhibition of state 3 respiration of liver mitochondria isolated from hibernating thirteen lined ground squirrels is eliminated when respiration is measured from saponin-permeabilized liver slices from the same animals, implying that the procedure might reverse mechanisms underlying metabolic suppression (K. Mathers and J.…”
Section: Estivating Ectothermsmentioning
confidence: 93%
“…The suppression of ROS production and the lack of oxidative damage previously observed in the disused skeletal muscle of aestivating frogs is consistent with this hypothesis (Reilly et al, 2014;Young et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Given that C. albogutatta demonstrate appreciably little muscle wasting during extended periods of aestivation, the mechanisms of proteolytic control in skeletal muscle remain an interesting and unexplored avenue. In a recent study ROS production was found be suppressed in the disused skeletal muscle of aestivating frogs, which was suggested to possibly protect against potential oxidative damage and preserve skeletal muscle mass during aestivation (Reilly et al, 2014) (Chapter 3).…”
Section: Introductionmentioning
confidence: 99%